MOBILIZATION AND CONSERVATION OF THE SEED POOL OF PLANT GENETIC RESOURCES IN AZERBAIJAN - Z. I. Akparov; S. A. Mammadova; A. T. Mammadov (Вавиловский журнал генетики и селекции)
The article is dedicated to fund-raising activities and the conservation of plant genetic resources in Azerbaijan. Brief information is provided on the activities of the National Gene Bank, functioning at the Institute of Genetics Resources of the Azerbaijan National Academy of Sciences, the foundation of the Information Centre and the development of a unified information system with a centralized database on Plant Genetic Resources in Azerbaijan.